Etiological Spectrum And Antibiotic Resistance Of Uropathogens In Various Forms Of Pyelonephritis: Clinical And Microbiological Research - Muradovna, Abdullaeva Aida; Asimovna, Kerimova Kabira; Shamilevich, Dibiraliev Akhmed; Abdulsemedovna, Abdulsemedova Jamilya; Fikretovna, Nabieva Leila; Mutalimovna, Ramazanova Muminat; Mansurovna, Dibirova Aminat; Imamovna, Shahmardanova Kamila; Mahachevna, Magomedova Maryam; Abdulkasumovich, Magomedov Alibek (Journal of Neonatal Surgery, 2025)
Pyelonephritis is one of the most common infectious and inflammatory diseases of the urinary system, with a high proportion of hospitalizations and the risk of chronicling the process. The purpose of this study was to analyze the etiological spectrum of pyelonephritis pathogens and determine their sensitivity to the main groups of antibacterial drugs in patients with acute and chronic forms of the disease. The study included 68 patients undergoing inpatient and outpatient treatment. A bacteriological analysis of urine was performed to identify the pathogens and determine their antibiotic sensitivity. It has been established that Escherichia coli remains the dominant pathogen, however, an increase in the proportion of Klebsiella spp., Enterococcus spp. and Pseudomonas aeruginosa is observed. A high degree of resistance to ampicillin, tetracycline and fluoroquinolones has been recorded, especially among nosocomial strains. The optimal first-line drugs are cephalosporins of the third generation and carbapenems. The results obtained confirm the need for regular microbiological monitoring and revision of local empirical therapy regimens, taking into account local resistance.